RETRACTED: Elsherif et al. Investigation of the Potential of Nebivolol Hydrochloride-Loaded Chitosomal Systems for Tissue Regeneration: In Vitro Characterization and In Vivo Assessment. Pharmaceutics 2021, 13, 700 - Noha Ibrahim Elsherif; Abdulaziz Mohsen Al-Mahallawi; Abdelfattah Ahmed Abdelkhalek; Rehab Nabil Shamma (Pharmaceutics)
The journal retracts the article “Investigation of the Potential of Nebivolol Hydrochloride-Loaded Chitosomal Systems for Tissue Regeneration: In Vitro Characterization and In Vivo Assessment” [...]